Korelasi antara Tingkat Kreativitas dan Hasil Belajar Bahasa Inggris Mahasiswa Politeknik Maritim Negeri Indonesia - Deri Herdawan (PPPM Polimarin, 2023)
As an international language, English is studied at various levels of education in Indonesia. In English teaching learning process, there are many factors that influence the outcome, one of which is the learner's factor. Creativity is a learner psychological aspect that has an important role. This research sought to identify the correlation between the learners’ creativity level and their Englih learning outcome. This quantitative research involved a research population of the learners from engineering study program during the 2022/2023 academic year. There were 47 students in the study program, thus the total sampling technique was used. The instrument for assessing learners' creativity level and their English scores were used to obtain the required data. The data were then analyzed using the Pearson Product Moment formula. The results of inferential statistical analysis using SPSS version 26 software obtained a correlation coefficient of (r = 0.96, p <0.001). This indicates that between the two variables being discussed (creativity level and English learning outcome) have a positive and significant correlation. The implications of the results from this research are discussed in detail in this article.